295. Outcomes of Orthopedic Hardware-Related Osteomyelitis Treated Via a County Hospital Outpatient Parenteral Antimicrobial Therapy (OPAT) Program. (26th November 2018) - Valinetz, Ethan; Beeler, Cole; Erdman, Sharon
Abstract: Background: Orthopedic hardware-related osteomyelitis (OHRO) is associated with high morbidity and cost from prolonged courses of antibiotics and additional surgery. There is limited published data describing OPAT for the treatment of OHRO. Methods: Electronic medical records of patients receiving OPAT for OHRO between July 1, 2009 and March 1, 2015 at Eskenazi Hospital were retrospectively reviewed. Data were collected using a standardized data collection form for 24 months after OPAT completion. Cure was defined as lack of clinical signs/symptoms of infection, CRP < 5 mg/L, absence of radiologic signs infection with hardware removal as planned (negative intraoperative cultures). Failure was defined as persistent clinical/laboratory signs of infection during/at the end of OPAT, unanticipated repeat surgery, isolation of new organism from removed hardware, or extension of OPAT due to continued infection. Safety of OPAT was evaluated through adverse event and line complication monitoring. Results: Overall, 53 patients (57% male) with OHRO were included (mean age of 50.5 ± 13.2 years). Two patients were excluded due to refusal of OPAT and death after a decision for comfort care. Of 30 evaluable patients who received OPAT with retained hardware, 14/30 (47%) achieved clinical cure. Five patients had failure requiring surgery during OPAT from worsening infection. 23/25 (92%) remaining patients with retained hardware received PO suppressive antibiotics until hardware removal; three failures were observed in patients noncompliant with PO suppression. Of 21 patients who received OPAT after hardware removal, 16 (76%) achieved clinical cure; five patients had failure due to extension of OPAT for 2–3 weeks due to continued features of infection. Three patients (6%) had an adverse event during OPAT (one each thrombocytopenia, vertigo, acute kidney injury) while three patients (6%) had line-related complications (2 bacteremias, one deep vein thrombosis). Conclusion: OPAT is a viable treatment option for ORHO when utilized in appropriate patients. Patients with retained hardware or noncompliance with oral suppressive therapy may be associated with increased failure. Further study is needed to validate these and other potential risk factors for treatment failure. Disclosures: All authors: No reported disclosures.